2021
DOI: 10.7717/peerj.12057
|View full text |Cite
|
Sign up to set email alerts
|

The stability of soil organic carbon across topographies in a tropical rainforest

Abstract: Mechanisms of soil organic carbon (SOC) stability are still unclear in forest ecosystems. In order to unveil the influences of topography on the SOC stability, a 60ha dynamic plot of a tropical montane rainforest was selected in Jianfengling, in Hainan Island, China and soil was sampled from 60 quadrats. The chemical fractions of the SOC were detected with 13C CPMAS/NMR and path analyses explore the mechanisms of SOC stability in different topographies. The chemical fractions of the SOC comprised alkyl carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…For deep soils (20-40 cm and 40-60 cm), the input of SOC is mainly from the leaching of surface SOC and a few roots. Since the soil clay proportions were higher in the study area (Jiang et al, 2021), there was less leaching of surface SOC to the deep soil. In addition, this study found a significant negative correlation between bulk density (BD) and SOC (Figure 2), which indicates that the high soil BD is also not conducive for the leaching of surface SOC to deep soil layers.…”
Section: Effects Of Forest Succession On Soil Organic Carbonmentioning
confidence: 87%
“…For deep soils (20-40 cm and 40-60 cm), the input of SOC is mainly from the leaching of surface SOC and a few roots. Since the soil clay proportions were higher in the study area (Jiang et al, 2021), there was less leaching of surface SOC to the deep soil. In addition, this study found a significant negative correlation between bulk density (BD) and SOC (Figure 2), which indicates that the high soil BD is also not conducive for the leaching of surface SOC to deep soil layers.…”
Section: Effects Of Forest Succession On Soil Organic Carbonmentioning
confidence: 87%
“…The stable liquid is expressed as a BOD/COD ratio close to 0.1 where each parameter has a concentration of less than 100 mg/L. The definition of stable quality [25], [26] is the insignificant change in BOD concentration due to the small BOD concentration. Between the two classes is a class of substances that can be decomposed by microbes or called biodegradable.…”
Section: Reactants Indicatormentioning
confidence: 99%